PRAKTEK SEWA LAHAN CABANG USAHATANI SAWI OLEH PETANI PENYEWA DI KAMPUNG SUSWENI DISTRIK MANOKWARI TIMUR KABUPATEN MANOKWARI - Parno N. Lumbantoruan; Els Tieneke R. Katmo; Yustina L.D Wambrauw (Sosio Agri Papua, 2020)
Susweni is the village that located in East Manokwari District in Manokwari Regency. Susweni is one of village that is centre of vegetables products and mustard green (Brassica Juncea L) is one potential comodity in this village. This comodity is planted by tenant farmers that come from Buton. The objectives of this studi are: 1). To describe land rent practise that done in Kampung Susweni and 2). To measure the eficiency of this comodity. The sampling method are consist of two stages :first stage is deliberate village election (purposive) and the second stage was random sampling. The result shows that there is no legal contract between tenants and land owners with different fee based on wide area. The rent is payed by money annualy arround 2,5 million rupias for 1 hecatre. In addition, the eficiency of farms is about 2,7 that means this farm give much profit for tenants.